Initiation and interruption in intravenous bisphosphonate therapy among patients with multiple myeloma in the United States. (8th December 2018) - McGrath, Leah J.; Hernandez, Rohini K.; Overman, Robert; Reams, Diane; Liede, Alexander; Brookhart, M. Alan; O'Donnell, Elizabeth
Abstract: Background: Prior to 2018, intravenous bisphosphonates (IV BPs) were the only therapies recommended to prevent skeletal‐related events for patients diagnosed with multiple myeloma (MM). We examined patterns of IV BP initiation and interruption among patients with newly diagnosed MM (NDMM) in the United States. Methods: Electronic health records linked to administrative health insurance claims were used to identify adults with NDMM between 1 January 2011 and 30 April 2016. Patients were excluded for recent IV BP use or concurrent cancer. The incidences of IV BP initiation and interruption were estimated using competing risk regression. A generalized linear model was used to estimate risk factors for treatment initiation and interruption. Results: Among the 547 patients with NDMM, 64% initiated MM therapy within 30 days of diagnosis. By one year, 65% (95% CI: 59, 70) of patients with appropriately timed anti‐MM therapy had initiated an IV BP. Zoledronic acid was the most commonly initiated IV BP. Patients with Stage III MM were more likely to initiate an IV BP (adjusted risk difference (RD): 6.3; 95% CI: 2.7, 10.1), while those with eGFR <30 mL/min were less likely to initiate (RD: −9.7; 95% CI: −13.8, −5.8). Of the 264 patients who initiated an IV BP, 77% (95% CI: 71, 82) experienced an interruption within one year. Patients on concurrent anti‐MM therapy were less likely to experience an interruption in IV BP therapy. Conclusions: Many patients with NDMM do not initiate IV BPs, particularly those with renal complications. Interruptions of IV BPs were common. Abstract : Data from routine clinical practice suggests that about 35% of patients with actively managed, newly diagnosed multiple myeloma did not receive intravenous bisphosphonates during the first year, even though these therapies have been shown to be effective in preventing SREs. The majority of patients who do initiate therapy, experience a treatment interruption within the first year after starting treatment.